Unlocking Private Sector Investment in Climate Smart Agriculture: Presentation at USAID Global Learning and Exchange Event, Asia - Siem Reap, Cambodia - Lundy, Mark M. (2016)
Exploration of how to incentivize private sector investment in climate smart agriculture and what role USAID can play in this process.